Analisis Konten Rokok di Situs Web Berbagi Video YouTube: User Engagement Analysis - Ramadona, Aditya; Mellen, Renie Cuyno; Najiyati, Ifa; Farahdilla, Zakiya Ammalia; Padmawati, Retna Siwi (Jurnal Kesehatan Komunitas, 2023)
Penetration of the internet and social media in Indonesia is increasing, with the most significant percentage of its users coming from the youth. The internet and social media can be a medium for promoting and selling products to youth. This study aimed to identify and describe videos potentially suggested when users enter the keyword "rokok" in a search on YouTube. We hypothesized that tobacco-related videos on YouTube could contain materials that either refer to (1) tobacco advertising, promotion, and sponsorship (TAPS); or (2) Non-TAPS categories. Both types of materials could have different engagement from the viewers. A YouTube search was performed in October 2022, and we only consider the videos published during June 2022. We assigned our team to classify the video content to the TAPS and Non-TAPS categories based on its title and description. We analyzed the number of views, likes, and comments of each video descriptively. We obtained 210 videos and excluded 24 videos unrelated to the study objectives in terms of the context or the language used. Most videos are related to TAPS (84%), and very few contain Non-TAPS (16%), in particular anti-smoking, including Public Service Advertisements (3%). Non-TAPS-related videos were mainly published by News Channels and the Government Public Relations Office Channels (57%), while individuals, including MSMEs and retailers, seemingly published most TAPS-related videos (78%). In addition, TAPS-related videos tend to have a higher number of likes and comments from viewers. YouTube is a potential medium to attract viewers and promote health, but TAPS-related videos are much easier to find. Public health agencies should establish a more significant presence on YouTube to reach more people and engage in broader partnerships to promote health educational material.